Institutional public private partnerships for core health services: evidence from Italy - Longo Francesco; Cappellaro Giulia (BMC, 2011)
Abstract Background Public-private partnerships (PPPs) are potential instruments to enable private collaboration in the health sector. Despite theoretical debate, empirical analyses have thus far tended to focus on the contractual or project dimension, overlooking institutional PPPs, i.e., formal legal entities run by proper corporate-governance mechanisms and jointly owned by public and private parties for the provision of public-health goods. This work aims to fill this gap by carrying out a comparative analysis of the reasons for the adoption of institutional PPPs and the governance and managerial features necessary to establish them as appropriate arrangements for public-health services provisions. Methods A qualitative analysis is carried out on experiences of institutional PPPs within the Italian National Health Service (Sistema Sanitario Nazionale, SSN). The research question is addressed through a contextual and comparative embedded case study design, assuming the entire population of PPPs (4) currently in force in one Italian region as the unit of analysis: (i) a rehabilitation hospital, (ii), an orthopaedic-centre, (iii) a primary care and ambulatory services facility, and (iv) a health- and social-care facility. Internal validity is guaranteed by the triangulation of sources in the data collection phase, which included archival and interview data. Results Four governance and managerial issues were found to be critical in determining the positive performance of the case examined: (i) a strategic market orientation to a specialised service area with sufficient potential demand, (ii) the allocation of public capital assets and the consistent financial involvement of the private partner, (iii) the adoption of private administrative procedures in a regulated setting while guaranteeing the respect of public administration principles, and (iv) clear regulation of the workforce to align the contracts with the organisational culture. Conclusions Findings suggests that institutional PPPs enable national health services to reap great benefits when introduced as a complement to the traditional public-service provisions for a defined set of services and goals.